2010
DOI: 10.1126/science.1195709
|View full text |Cite
|
Sign up to set email alerts
|

Spin Transfer Torques in MnSi at Ultralow Current Densities

Abstract: Spin manipulation using electric currents is one of the most promising directions in the field of spintronics. We used neutron scattering to observe the influence of an electric current on the magnetic structure in a bulk material.In the skyrmion lattice of MnSi, where the spins form a lattice of magnetic vortices similar to the vortex lattice in type II superconductors, we observe the rotation of the diffraction pattern in response to currents which are over five orders of magnitude smaller than those typical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
1,149
2
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,174 publications
(1,203 citation statements)
references
References 30 publications
14
1,149
2
7
Order By: Relevance
“…It was experimentally demonstrated that ultralow current density of B10 5 -10 6 A m À 2 , orders of magnitude smaller than the current density typically used for the domain-wall manipulation, can drive translational and rotational motions of SkX domains in MnSi (ref. 18) and FeGe (ref. 19).…”
mentioning
confidence: 99%
“…It was experimentally demonstrated that ultralow current density of B10 5 -10 6 A m À 2 , orders of magnitude smaller than the current density typically used for the domain-wall manipulation, can drive translational and rotational motions of SkX domains in MnSi (ref. 18) and FeGe (ref. 19).…”
mentioning
confidence: 99%
“…These topologically protected properties, together with their nanoscale dimensions (10 ~ 100 nm) and ultralow threshold for current-driven motion (10 5 ~ 10 6 Am -2 ) [17][18][19] , make the magnetic skyrmions be promising materials for technological applications in spincronic devices [20] .…”
mentioning
confidence: 99%
“…In bulk samples, skyrmions form three-dimensional (3D) line objects and occur in a limited range of fields and temperatures 2,16 , while for thin samples the skyrmions exhibit two-dimensional (2D) properties and are stable over a much larger range of fields and temperatures extending close to room temperature [4][5][6][7] . Skyrmions can be set into motion through the application of an external current 7,10,[18][19][20] , and it has been shown that there is a critical current above which the skyrmions depin into a sliding state [19][20][21][22][23][24][25][26] . Skyrmion motion can be directly observed with Lorentz microscopy 7,10 or deduced from changes in the transport properties, permitting the construction of effective skyrmion velocity versus applied force curves that show that the skyrmion velocity increases with increasing current 20 .…”
Section: Introductionmentioning
confidence: 99%